Beta-Adrenergic Agonists - Giovanni Barisione; Michele Baroffio; Emanuele Crimi; Vito Brusasco (MDPI AG, 2010)
Inhaled β2-adrenoceptor (β2-AR) agonists are considered essential bronchodilator drugs in the treatment of bronchial asthma, both as symptoms-relievers and, in combination with inhaled corticosteroids, as disease-controllers. In this article, we first review the basic mechanisms by which the β2-adrenergic system contributes to the control of airway smooth muscle tone. Then, we go on describing the structural characteristics of β2-AR and the molecular basis of G-protein-coupled receptor signaling and mechanisms of its desensitization/ dysfunction. In particular, phosphorylation mediated by protein kinase A and β-adrenergic receptor kinase are examined in detail. Finally, we discuss the pivotal role of inhaled β2-AR agonists in the treatment of asthma and the concerns about their safety that have been recently raised.